A Puzzle about Normativity - Giovanni Rolla (Principia: An International Journal of Epistemology)
In this paper, I present a possible solution to the puzzle unveiled by Kornblith (2012) about the sources and the possibility of knowledge of epistemic norms. The puzzle is: if such norms cannot be discovered solely by reflection (“looking inwards”, thinking about first-order thoughts), and if there are correct ways of thinking and inferring, then such norms can only be discovered by investigating the world (“looking outwards”) —a counterintuitive conclusion. To avoid skepticism about normativity, I argue that we create normative correctness and discover normative demands by investigating the world and reflecting about our epistemic practices. This is done by an exposition of the method known as reflective equilibrium, which is defended against Kornblith’s thesis that the appeal to reflective equilibrium is doomed to failure because it implies reflection.